Dalits in regional context - Puri Harish K (Jaipur Rawat, 2004)
This volume brings together specially written articles based on recent studies relating to various dimensions of change in the position of Dalits and their present day living experience in Punjab. These cover a wide range - demographic position; the impa
Keywords: Dalits; India; Punjab